Use of urinalysis as a screening tool for asymptomatic infants. Issue 6 (25th April 2013) - Bereket, Gamze; Bozdogan, Gunseli; Saribeyoglu, Ebru; Arapoglu, Mujde; Serteser, Mustafa; Celiker, Alpay
<x xml:space="preserve">Abstract</x> Aim The utility of screening urinalysis in asymptomatic children has been questioned based on studies done in school‐age children or adolescents. The American Academy of Pediatrics (AAP) recommended to abandon this screening in 2007 but many paediatricians perform it at some point during childhood. Thus, we aimed to investigate usefulness of screening urinalysis during infancy. Methods We retrospectively reviewed results of screening urinalysis done in infants at 6–18 months of age who had regular care since birth at our centre. Infants with an ICD‐10 (International Classification of Diseases, Tenth Revision) diagnostic code for routine child health exam (Z00.1) and a urinalysis requested with this code on the same date were included. Results A total of 683 infants met the inclusion criteria. 44 (6%) had an abnormal urinalysis. The most common abnormality (n = 39, 5, 7%) was pyuria. Of these 39 babies, 5 had a repeat urinalysis only, 18 had a repeat urinalysis with urine culture, and 16 had a urine culture alone. Six patients had positive culture results and were given antibiotic treatment. All six babies who received treatment had normal ultrasound and two patients had a voiding cystourethrography, which were also normal. The other abnormalities (n = 5) detected were microscopic hematuria and proteinuria. Repeat urinalyses of these patients were normal. Conclusion Screening urinalysis results were abnormal in 6% of the babies, but in 86% of those, abnormalities were transient. Only <1% had positive culture results. These data add to the evidence that screening urinalysis during infancy is unjustified supporting the AAP 2007 recommendations.